PERANCANGAN DAN IMPLEMENTASI WEBSITE PENDAFTARAN PASIEN THERAPY CENTER AKU BISA PEKANBARU - Indi Sabila; Rahma Hanum; Muhammad Firjatullah Akhbar (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
This report discusses the Integration II project titled "Design and Implementation of the Aku Bisa Pekanbaru Therapy Center Patient Registration Website." Aku Bisa Pekanbaru is a Therapy Center for children with special needs. However, the manual registration system currently in use leads to long queues and extended waiting times. To address this issue, a web-based registration system was developed, allowing parents to register their children online without needing to visit the center in person. The website is also equipped with an online payment system using Midtrans as the payment gateway, enabling secure and convenient transactions. The system development process includes requirements analysis, user interface design, feature implementation, and testing to ensure functionality and security. The results of this project indicate that the developed website enhances the efficiency of therapy services, accelerates the registration and payment process, and provides comprehensive information about available services. Additionally, the utilization of this website helps expand marketing reach and strengthens the credibility of Aku Bisa Pekanbaru as a professional and trusted Therapy Center in the community.